Efeitos do treinamento funcional sobre a composição corporal de idosos - Monteiro, Marcos Raphael Pereira (2022)
Body composition is a good health indicator for older people, related to autonomy and mortality. Specifically, during aging, two events stand out: the reduction of lean body mass and the increase of body fat. On the other hand, functional training (FT) has been highlighted in recent years in health promotion for older people, however, its effects on body composition are not well established yet. Thus, the objective of this dissertation was to analyze the effect of functional training on body composition variables in the elderly. For this, two distinct studies were conducted. First, we conducted a systematic review of the literature with the following guiding question: "What are the effects of functional training on lean mass and body fat in the older population?" establishing the acronym PICOT as P: Older people; I: Functional training; C: Other exercise interventions or no comparison; O: Lean mass and body fat; T: Randomized clinical trials. The search for studies was conducted in the Pubmed, Scopus, Web of Science, Cochrane Library, and Google Scholar databases, and the risk of bias was assessed using the PEDro scale. In a second step, a randomized controlled trial was conducted with a total duration of 16 weeks that had 96 participants randomized into three distinct groups: FT (n = 32, 63.9 ± 3.8 years; 28.67 ± 4.83 kg/m²); combined training (CT) (n = 32; 64.9 ± 4.0 years; 27.76 ± 4.36 kg/m²); and control group (CG) (n = 32; 67.5 ± 5.9 years; 28.52 ± 6.34 kg/m²). Body composition measurements were evaluated by bioimpedance and checked every four weeks, totaling five evaluations. Regarding the systematic review, of the 3956 studies identified in the literature, only five studies were included according to the eligibility criteria listed. Of these, only two studies had a low risk of bias. The studies that presented interventions lasting between 5 and 6 months promoted reduced body fat and increased lean mass, whereas interventions lasting between 10 and 12 weeks presented conflicting results. As for the clinical trial, it was verified an increase in lean mass in the eighth week of training (TF: Δ = +1,77%, TC: Δ = +1,54%), and in the twelfth week it was verified a reduction in the percentage of fat (TF: Δ = - 3,2%, TC: Δ = - 4,3%) and an increase in the appendicular lean mass (TF: Δ = +2,31% TC: Δ = +2,37%) of the older women. These changes in body composition lasted until the end of the intervention. In conclusion, the literature points out that interventions lasting between 5 and 6 months show positive adaptations in the body composition of the elderly; however, there are still few high-quality studies in the literature that can provide a higher level of evidence regarding the effects of FT on the body composition of this population. On the other hand, the FT seems to have similar effects to the CT on the adaptations promoted in the body composition of older women, increasing lean mass from the eighth week of training and decreasing body fat from the twelfth week of intervention.